miR-15a and miR-20b sensitize hepatocellular carcinoma cells to sorafenib through repressing CDC37L1 and consequent PPIA downregulation - Li Li; Shijun Yu; Jingde Chen; Ming Quan; Yong Gao; Yandong Li (Cell Death Discovery, 2022)
Abstract Sorafenib is a classical targeted drug for the treatment of advanced hepatocellular carcinoma (HCC), but intrinsic resistance severely limited its therapeutic effects. In the present study, we aimed to identify crucial genes in HCC cells that affect sorafenib resistance by a CRISPR/Cas9 genome-scale screening. The results indicated that the deficiency of miR-15a and miR-20b contributed to sorafenib resistance, whereas exogenous expression of miR-15a and miR-20b enhanced sorafenib sensitivity of HCC cells by cell viability, colony formation, and flow cytometry analyses. Further analyses revealed that cell division cycle 37 like 1 (CDC37L1) as a common target of miR-15a and 20b, was negatively regulated by the two miRNAs and could enhance sorafenib resistance of HCC cells in vitro and in vivo. Mechanistically, CDC37L1, as a cochaperone, effectively increased the expression of peptidylprolyl isomerase A (PPIA) through strengthening the binding between heat shock protein 90 (HSP90) and PPIA. The results from immunohistochemical staining of a HCC tissue microarray revealed a positive association between CDC37L1 and PPIA expression, and high expression of CDC37L1 and PPIA predicted worse prognosis of HCC patients after sorafenib therapy. Taken together, our findings reveal crucial roles of miR-15a, miR-20b, CDC37L1, and PPIA in sorafenib response of HCC cells. These factors may serve as therapeutic targets and predict prognosis for HCC treated with sorafenib.